The Influence of Product Quality, Word Of Mouth, and Brand Trust on Purchasing Decisions for Marina Hand & Body Lotion Marina among Students at the Faculty Of Economics and Business UNP Kediri - Wahyuningsih, Rohmah; Subagyo (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This research sought to evaluate the influence of product quality, word of mouth, and brand trust on purchasing decisions, both partially and simultaneously. Design/Method/Approach : This research adopts a quantitative approach grounded in a causal method. The study focuses on students from the Faculty of Economics and Business at UNP Kediri, with a sample of 40 respondents who are users of Hand & Body Lotion Marina. Data collection was done using an online survey through a questionnaire filled out by respondents on a Likert scale. The data analysis technique uses multiple linear regression analysis. Research findings : The outcome of this research show that product quality and brand trust have a significant effect, while word of mouth has no significant effect.. Theoretical contribution/Originality : This study can be a reference for future study to the affect of product quality, word of mouth, and brand trust on the purchase decision of Marina Hand & Body Lotion Practitioner Implications/ Policy : This is expected to help Marina in formulating an effective marketing strategy by utilizing product quality, word of mouth and brand trust to improve consumer purchasing decisions. Research limitations : This study focuses on the analysis of how product quality, word of mouth, and brand trust affect the purchasing decisions of Marina Hand & Body Lotion among students at the Faculty of Economics and Business, UNP Kediri.